La valeur de la science - Poincaré, Henri 1854-1912; Vuillemin, Jules 1920-2001 (Paris Flammarion, 1970)
The book deals with questions in the philosophy of science and adds detail to the topics addressed by Poincaré's previous book, 'La science et l'hypothese' (1902). The first part of the book deals exclusively with the mathematical sciences, and particularly, the relationship between intuition and logic in mathematics. It first examines which parts of science correspond to each of these two categories of scientific thought, and outlines a few principles:- What we define as intuition changes with the course of time (Classical philosophers were seen as logicians in their time, but today we might think of them as using intuition) – it is therefore the ideas that change, in the evolution of scientific thought;- This evolution began with the arithmetization of analysis, and ended with the revival of intuitive ideas in an axiomatic system, by the first (true) logicians.In the second part of his book, Poincaré studies the links between physics and mathematics. His approach, at once historical and technical, illustrates the preceding general ideas.
Jules Henri Poincaré (1854-1912) was a French mathematician, theoretical physicist, engineer, and philosopher of science. He is often described as a polymath, and in mathematics as "The Last Universalist", since he excelled in all fields of the discipline as it existed during his lifetime.
Originally published in 1905.
Keywords: 20th Century (1901-2000); Science; Philosophy; France